2012
DOI: 10.1111/j.1440-1746.2012.07145.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral efficacy of lamivudine versus entecavir in patients with hepatitis B virus‐related advanced hepatocellular carcinoma

Abstract: The antiviral efficacy of LAM and ETV was similar and the type of antiviral agent did not influence overall survival in patients with HBV-related advanced HCC. Thus, LAM, which is less expensive than ETV in Korea, might be sufficient to control HBV in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Commonly used NAs include lamivudine (LAM), telbivudine, adefovir (ADV), entecavir (ETV), and tenofovir disoproxil fumarate (TDF). Different NAs seem to have a similar antiviral effect in HBVrelated HCC patients [62]. Less selective NAs, such as gemcitabine and 5-FU, are used as anti-tumor chemotherapy medications.…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 99%
“…Commonly used NAs include lamivudine (LAM), telbivudine, adefovir (ADV), entecavir (ETV), and tenofovir disoproxil fumarate (TDF). Different NAs seem to have a similar antiviral effect in HBVrelated HCC patients [62]. Less selective NAs, such as gemcitabine and 5-FU, are used as anti-tumor chemotherapy medications.…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 99%
“…Antiviral agents, such as lamivudine and adefovir have been found to improve cirrhotic liver function in some studies (Aspinall, et al 2011) but have not been shown to have anti-carcenogenic effects in other studies (Kwon and Lok 2011; Peng, et al 2012). In addition, there is evidence that these anti-viral agents have little effect on survival of patients with advanced-stage disease (Shin, et al 2012) or on disease recurrence after hepatectomy for HCC (Chan, et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a less potent drug was reported to be equally effective as entecavir in advanced HCC patients 26,27. Shin et al 27.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al 27. compared 87 patients treated with lamivudine to 47 patients treated with entecavir, and they reported that the virological response and overall survival were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation